Sobolev LVG analysis of prebiotic molecule formamide (NH2CHO) found in the ISM - Sharma, M. K.; Mampatta, V. D.; Chandra, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Using known values of rotational and centrifugal distortion constants in conjunction with electric dipole moment of NH2CHO, we have calculated energies of rotational levels in the ground vibrational state, and the probabilities for radiative transitions between the levels. Используя известные значения констант вращательного и центробежного дисторсий вместе с электрическим дипольным моментом NH2CHO, мы рассчитали энергии вращательных уровней в основном колебательном состоянии и вероятности радиационных переходов между уровнями.
Keywords: Astrophysics